THE INFLUENCE OF GUIDED INQUIRY LEARNING ASSISTED FLASH APPLICATION ON ELECTROLYTE SOLUTION MATERIALS AGAINST THE RESULTS OF STUDENTS - Dewi, Ratna Kumala; Haryani, Sri; Wardani, Sri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This study aims to determine how much influence of guided inquiry learning assisted flash application on electrolyte solution materials to the results of student class X learning in SMA Negeri 8 Semarang. This research method using an experimental method. The sampling technique used cluster random sampling technique. Method of data collection was done with documentation to find out the population, questionnaire for student responses, test (pretest and posttest), and observation to assess aspects of affective and psychomotor learning outcomes. Hypothesis test used in this research is an analysis of influence between variables, a test of difference of two means, and coefficient of determination. The result of different test of two mean value of posttest tcount is 6.68 more than ttable 1.995 with dk = 70 and 5% significance level mean that experiment class learning result is higher than control class. Implementation of guided inquiry learning model with flash application contributes 64% of student learning outcomes. Display of flash application using Software Adobe Flash CS 6. Based on the results of research, can be concluded that guided inquiry learning assisted flash application has a positive effect on student learning outcomes in SMA Negeri 8 Semarang on the material of electrolyte and nonelectrolyte solution.